(untitled) (Cardiovascular Journal, 2017)
Background: Hypertension is an emerging risk factor for developing heart failure with preserved ejection fraction (HFpEF). Diastolic dysfunction most frequently associated with a subclinical impairment of systolic function in patients with HFpEF. The aim of this study was to detect early impairment of left ventricular function in hypertensive patients with preserved ejection fraction using Tissue Doppler Imaging (TDI). Methods: This cross-sectional study included a total 105 subjects who were divided into three groups (group-1: 35 healthy control; group-2: 35 hypertensive patients without concentric left ventricular hypertrophy, and group-3: 35 hypertensive patients with concentric left ventricular hypertrophy having left ventricular ejection fraction (LVEF)>50% on 2D echocardiography). They underwent TDI to measure systolic dysfunction by systolic annular velocity during systole (S´) and diastolic dysfunction by diastolic filling pressure (E/E´). Results: The results were obtained in 105 subjects: group-1 (40.63±5.0years; 34.4% male); group-2 (49.57±9.7years; 34.4% male) and group-3 (55.17±8.5years; 31.2% male). LVMI and RWT were significantly higher (p<0.001) in both hypertensive groups. The presence of systolic dysfunction by TDI as evidence by systolic annular velocity (S´) was significantly reduced (p<0.001) in both hypertensive groups compared to controls (0.08±0.11 vs.06±0.01 vs. 0.05±0.01).The presence of diastolic dysfunction by TDI as evidence by diastolic filling pressure (E/E´) were significantly higher (p<0.001) in both groups of hypertensive patients. There was significant correlation between E/E´ and S´(r = -593; p= <0.001). Conclusion: TDI provided a new insight into impaired systolic function by detecting lower values of S´ and impaired diastolic function by detecting higher values of E/E´ in hypertensive patients. This study was a clear reflection of early impairment of LV function in hypertensive patients (with or without C-LVH) and it might be helpful for identifying hypertensive patients who are at high risk for heart failure. Cardiovasc. j. 2017; 9(2): 147-154